Sunnah Al-Ibtilā' Hikamuha wa Atharuhā fī Tamkīn al-Ummah min Manẓūr al-Qur'ān al-Karīm - Hamid., Afaf 'Abd Al-Ghafur (Jurnal Usuluddin, 2009)
Allah S.W.T. created all things according to certain decrees and nothing could happen out of its rulings. Allah’s divine decree has a significance in dealing with mankind; their attitude towards the law of Allah and His messengers; and the impacts on this world and the hereafter. The main method to understand Allah’s decree is by referring to the Qur’an and Prophet’s Sunnah. Tribulation is one of His advantageous decrees in selecting the most pious man in order to find out who really serve Him. This article tries to reveals this kind of decree according to the Qur’an, followed by an introduction defines tribulation and its related meanings. The first part discusses general and specific of tribulation’s nature and forms; whilst the second part discusses the wisdom behind it and its impact on global stability, both general and specific.